PEMBARUAN PENDIDIKAN ISLAM: TELAAH RETROSPEKTIF DAN PROSPEKTIF - Maidar Maidar (Islam Futura, 2015)
Islamic reform however which be conducted at the moment, should be started through education as education is the key to open the door of modernization. Therefore, the thinkers of Islamic education, Islamic education needs to rethink both retrospective and prospective. Retrospective is about the changes of educational form in the past. While the prospective is about the changing of the educational process in the future, namely the idea and Islamic education reform programs which have the link roots to modernization thought and Islamic civilization as a whole. It has relationship and link to reformation (tajdid) that is to revive the Islamic faith. It is the basis of belief that reform movements remain a legitimate part of the original and the description of Islam at the stage of the history.